Effect of acid dopants in biodegradable gel polymer electrolyte and the performance in an electrochemical double layer capacitor. (26th August 2015) - Sudhakar, Y N; Selvakumar, M; Krishna Bhat, D
Abstract: Proton-conducting biodegradable gellan gum gel polymer electrolytes (GPEs) have been prepared using three different dopants, namely ortho-phosphoric (o-H3 PO4 ), sulfuric (H2 SO4 ) and hydrochloric acids (HCl). The GPEs were cross-linked using borax. The polymeric gels were characterized by spectroscopic, thermal, ionic conductivities and dielectric measurements. Proton conductivity was in the range of 5.1 × 10 −3 to 3.7 × 10 −4 s cm −1 and activation energies were between 0.14 meV and 0.19 meV, at different temperatures. Among the doped acids, the H3 PO4 doped GPE exhibited thermal stability at varying temperature. Electrochemical double layer capacitors (EDLCs) were fabricated using activated carbon as electrode material and GPEs. The EDLCs were tested using cyclic voltammetry, ac impedance spectroscopic and galvanostatic charge-discharge techniques. The maximum specific capacitance value was 146 F g −1 at a scan rate of 2 mV s −1 . Quite stable values were obtained at a constant current density up to 1000 cycles.